Correction: An electronic enzyme-linked immunosorbent assay platform for protein analysis based on magnetic beads and AlGaN/GaN high electron mobility transistors. Issue 13 (4th June 2021) - Wang, Jin; Gu, Zhiqi; Liu, Xinsheng; Zhao, Lei; Peng, Huoxiang; Li, Jiadong
Abstract : Correction for 'An electronic enzyme-linked immunosorbent assay platform for protein analysis based on magnetic beads and AlGaN/GaN high electron mobility transistors' by Jin Wang et al., Analyst, 2020, 145, 2725–2730, DOI: ; 10.1039/C9AN01809C .